2015
DOI: 10.1007/s00384-015-2293-8
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic stoma mesh did not prevent parastomal hernias

Abstract: A prophylactic stoma mesh did not reduce the rate of clinically or computed tomography-verified parastomal hernias. High BMI was associated with an increased risk of parastomal hernia formation regardless of prophylactic stoma mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
1
28
0
7
Order By: Relevance
“…8 In addition and interestingly, in a very recent observational study with more than 200 patients receiving a prophylactic keyhole synthetic mesh, the authors conclude that a prophylactic stoma mesh did not reduce the rate of clinically or CT-verified PHs. 20 To our knowledge, specific recommendations regarding the rationale of the material or the surgical technique for prosthetic reinforcement of stomas are lacking. Biologic mesh cannot be currently considered a gold standard in PH prevention or repair.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition and interestingly, in a very recent observational study with more than 200 patients receiving a prophylactic keyhole synthetic mesh, the authors conclude that a prophylactic stoma mesh did not reduce the rate of clinically or CT-verified PHs. 20 To our knowledge, specific recommendations regarding the rationale of the material or the surgical technique for prosthetic reinforcement of stomas are lacking. Biologic mesh cannot be currently considered a gold standard in PH prevention or repair.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to the review by Shabbir and colleagues, several small RCTs continued to lend support to prophylactic mesh use; however, most recently, in 2015, evidence emerged to the contrary. First, a large randomized trial found no reduction in parastomal herniation with mesh, and another large, long‐term observational study reported a similar result.…”
Section: Introductionmentioning
confidence: 97%
“…Los FR no técnicos son los siguientes: obesidad 6,7,9,18,27,28 , edad avanzada 4,6,7,9,29 , diabetes mellitus 9 , uso de corticoides 3,4,6,7,29 , enfermedad pulmonar crónica 4,6,7,9,29 , malnutrición 3,4,6,7,29 , perímetro abdominal mayor de 100 cm 30 , espesor del tejido subcutáneo mayor o igual a 23 mm 12 , infección de la herida 3,4,6,7,29 y la presencia de otras hernias de la pared abdominal 9,27 . La enfermedad de Crohn también aparece asociada a mayor riesgo de HP, aunque no así la colitis ulcerosa 8 .…”
Section: Factores Derivados Del Pacienteunclassified
“…En la bibliografía publicada, los resultados de las diferentes técnicas y mallas utilizadas como profilaxis de la HP son muy heterogéneos 47,61,62 . En la mayoría de los estudios se observa una disminución de la incidencia de HP al usar una malla profilác-tica 12,27,[63][64][65][66][67][68] , en algunos solo se evidencia una disminución de la incidencia detectada clínicamente, pero no por tac 69 , y en otros no se objetiva ni reducción clínica ni radiológica 28,70 (tabla 3). La mayoría de estos grupos colocan la malla retromuscular en cirugía abierta 27,63,64,65,67 , que ha demostrado ser factible y disminuir la incidencia de HP.…”
Section: Técnicas Preventivas Con Mallaunclassified
See 1 more Smart Citation